Study of the influence of fermentation conditions on the content of aroma-forming substances in young red wines - L. V. Gnetko; M. M. Udychak; M. M. Kobleva; B. B. Siyukhova (Новые технологии, 2023)
One of the main requirements for young wines is preservation the qualities of the grapes, including the bright varietal aroma characteristic of essential oils concentrated in the grape skins. At the same time, in the formation of the aroma of wine, substances synthesized by the enzyme systems of yeast cells are involved in the process of alcoholic fermentation. The main factors influencing the formation and ratio of aroma-forming substances in wine are the composition of the substrate, the race of yeast and the conditions for the fermentation process. Therefore, studies of the influence of the conditions of the fermentation process in the production of young red wine materials on the chemical composition of the aroma-forming components of wine are relevant. The analysis of the data obtained indicates the influence of the methods of carrying out the alcohol process on the content of aroma-forming compounds: aldehydes, ketones, higher and polyhydric alcohols, esters and fatty acids. It has been shown that the fermentation of the pulp wort, unlike carbon dioxide maceration, leads to a greater accumulation of oxidation products: acetaldehyde, acetoin and diacetyl, and also contributes to a higher content of higher alcohols. Under conditions of carbon dioxide maceration, a significant accumulation of aromatic alcohol – phenylethanol occurs. The conducted studies have shown that the use of carbon dioxide maceration using the Moldova grape variety generally has led to a significantly lower formation of oxidation products of both wort components and fermentation products. The additional introduction of carbon dioxide contributed to a decrease in the RH potential of the fermenting wort, which stimulated the accumulation of substances in a reduced form. At the same time, the content of esters in the case of artificial maceration is higher than under normal conditions, which indicates more intense enzymatic esterification reactions.It has been established that carbon dioxide maceration, in comparison with the classical processing of grapes, contributes to a greater formation and extraction of favorable aromatic components, and the additional introduction of carbon dioxide enhances this process.